Lay-therapist-delivered, low-intensity, psychosocial intervention for refugees and asylum seekers (PROSPER): protocol for a pilot randomised controlled trial - Rebecca Rawlinson (Trials, 2020)
Abstract Background Asylum seekers and refugees (AS&Rs) experience impaired mental health and wellbeing, related to stresses in their country of origin, experiences in transit and reception on arrival, including significant barriers to accessing mainstream services. Their contact with health care is often crisis-driven and mediated through non-governmental organisations (NGOs). Problem Management Plus (PM+) is a psychosocial intervention recommended by the World Health Organisation to address distress experienced by adults affected by humanitarian crises. We are investigating its application for the first time in a high-income country. Methods In a pilot randomised controlled trial (RCT), PM+ will be delivered to AS&Rs in contact with NGOs in Liverpool City Region, UK by lay therapists who have lived experience of forced migration. Following systematic review and stakeholder engagement, PM+ has been adapted to the local context, and lay therapists have been trained in its delivery. We will assess the feasibility of conducting a three-arm RCT of five 90-min sessions of PM+, delivered individually or in groups by lay therapists to AS&Rs experiencing emotional distress and functional impairment, compared with each other and with usual support offered by local NGOs. Distress and impairment at baseline will be measured by the Hospital Anxiety and Depression Scale (HADS) and the WHO Disability Assessment Schedule (WHO-DAS). We aim to recruit 105 participants, 35 per arm. Primary health outcomes are anxiety and depressive symptoms at 3 months, measured by HADS. Secondary outcomes include subjective wellbeing, functional status, progress on identified problems, presence of post-traumatic stress disorder and depressive disorder and service usage. Longer-term impact will be assessed at 6 months post baseline, on the same parameters. We will assess the feasibility of conducting a full RCT in relation to the following elements: recruitment and retention of lay therapists and study participants; fidelity of delivery of PM+; and suitability of the study measures, including any linguistic or cultural barriers. Discussion We will use these findings to specify the parameters for a full RCT to test the effectiveness and cost-effectiveness of PM+ in reducing emotional distress and health inequalities, and improving functional ability and wellbeing, amongst asylum seekers and refugees. Trial registration ISRCTN, ID: ISRCTN15214107 . Registered on 10 September 2019.